Musculoskeletal Disorders among Iranian Coal Miners at 2014 - Mashallah Aghillinejad; Elaheh Kabir Mokamelkhah; Mohammad Nassiri-Kashani; Mohammad Kazem Nouri; Narges Noorian; Amir Bahrami-Ahmadi (Iranian Journal of Health, Safety and Environment, 2016)
Some factors such as stooping posture and frequent kneeling in miners can increase prevalence of their musculoskeletal disorders Present study was performed for assessment of MSDs prevalence among Iranian coal miners and finds its relationships with some their characters including age, work experience and body mass index. Participants in the persent cross sectional study, were 505 coal miners which selected among Iranian coal miners by simple random method. Data of musculoskeletal disorders (MSDs) gathered by Standardized Nordic self-reporting questionnaire. Demographic and work related data were collected into the check list. Findings of persent study showed that 56.1% and 66.5% of study miners claimed one of the MSDs complaints during last week and in the last year respectively. Lumbar, Knee(s) and Back had most common MSDs prevalence at last week and year. MSDs prevalence had significant association with age (P≤0.02) and non-significant association with BMI (P≥0.8) of workers. MSDs in Iranian coal miners were happened in high rate. Ergonomic interventions strategies in the workplaces must be focussed for elimination of environmental hazards such as apposition at the time of work, manual handling of heavy loads.